KONSTRUKSI KURIKULUM ISLAM DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - AHMAD CHAFIDUT TAMAM; M YUNUS ABU BAKAR (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
Abstract: Islamic education curriculum is an activity that includes philosophy (thoughts) various detailed student activity plans in the form of forms of educational material, suggestions for teaching and learning strategies and things that include activities aimed at achieving the desired goals with reference to values. Islamic teachings. The Islamic education curriculum must highlight religion and morals in its various purposes. The content and scope of the Islamic education curriculum is comprehensive which reflects the spirit of Islamic thought and teachings that are universal and reach all aspects of life, both intellectual, psychological, social and spiritual, having a relative balance in the environment. in its scientific content, both the Shari'a sciences, the science of reason and language and the arts, includes all the subject matter needed by students, both religious and worldly. The Islamic education curriculum must be based on religious, philosophical, social, and psychological foundations. The contents of the Islamic education curriculum are mostly in the form of religious sciences such as the knowledge of the Qur'an, Hadith, Fiqh and Sufism in addition to not forgetting the sciences of the world.